Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2: \(=\dfrac{-2}{75}+\dfrac{5}{39}=\dfrac{33}{325}\)
3: \(=\dfrac{6}{11}\left(\dfrac{4}{9}+\dfrac{5}{9}\right)=\dfrac{6}{11}\)
4: \(=\dfrac{7}{19}\left(\dfrac{5}{13}+\dfrac{8}{13}-1\right)=-2\cdot\dfrac{7}{19}=-\dfrac{14}{19}\)
5: \(=\dfrac{2}{7}\left(\dfrac{4}{23}-\dfrac{27}{23}+1\right)=0\)
6: \(=\dfrac{3}{8}\left(\dfrac{3}{7}+\dfrac{4}{7}\right)+\dfrac{11}{8}=\dfrac{3}{8}+\dfrac{11}{8}=\dfrac{14}{8}=\dfrac{7}{4}\)
1) x - 2 = -6
x = -6 + 2
x = -4
2) -5 . x - ( -3 ) =13
-5 . x = 13 + ( -3 )
-5 . x = 10
x = 10 : ( -5 )
x = -2
Bài 1:
5; (-23) + 105
= 105 - 23
= 82
6; 78 + (-123)
= 78 - 123
= - (123 - 78)
= - 45
bài1
1)2763 + 152 = 2915
2)-7 +(-14)
=-(14 +7)
=-21
Bài 1 : bạn tự làm
Bài 2 :
1) (15+37)+(52-37-17) = 15 + 37 +52 - 37 - 17 = 50
2) (38 - 42 +14 ) - (25 - 27 -15 ) = 38 -42 +14 -25 +27 +15 = 27
3) - (21 - 32) - (-12 +32) = -21 +32 +12 -32 = -9
4) - (12 +21 -23) - (23 -21 +10) = -12 -21 +23 -23 +21 -10 = -22
5) (57-725) - (605 -53 ) = 57 -725 - 605 +53 = -1220
6) (55 +45 +15) - (15 -55 +45) = 55 +45 +15 -15 +55 -45 = 110
7) (35 +75) + (345 -35 -75) = 35 +75 +345 -35 -75 = 345
8) (2002 -79 +15) - (-79 +15 )= 2002 -79 +15 +79 -15 = 2002
9) -(515 -80 +91) - (2003+80-91) =-515+80-91-2003-80+91=-2518
10) 25-(-17) +24 -12 = 25 +17 +24 -12 = 54
11) 235 - (34 +135) -100 = 235 - 34 -135 -100 = -34
12) (13 +49 ) - (13 -135 +49) = 13 +49 -13 +135 -49 =135
13) (18 +29) + (158 -18 -29) = 18 +29 +158 -18 -29 = 158
Bài 3:
1) (-37)+14+26+37 = (14+26)+37-37 = 40
2) (-24) +10+6+24 = (10 +6) +24 -24 = 16
3) 15 +23 + (-25 )+(-23) = (15-25)+(23-23) = -10
4) 60+33+(-50) + (-33) = (60-50)+(33-33) = 10
5) (-16)+(-209)+(-14) +209 = (-16-14)+(209-209) = -30
6) (-12)+(-13)+36+(-11) = (-12-13-11)+36 = (-36)+36 = 0
7) -16 +24 +16 -34 = (-16 +16)+(24-34) = -10
8) 25 +37-48-25-37 = (25-25)+(37-37)-48 = -48
9) 2575+37-2576-29 = (2575-2576)+(37-29)= -1+8 = 7
10) 34+35+36+37-14-15-16-17= (34-14)+(35-15)+(36-16)+(37-17)
= 20+20+20+20 = 80
11) 4573+46-4573+35-16-5= (4573-4573)+(46-16)+(35-5)
= 30 +30 = 60
12) 32+34+36+38-10-12-14-16-18
= (32-12)+(34-14)+(36-16)+(38-18)-10
= 20+20+20+20-10 = 70
5^x + 5^ ( x + 2 ) = 650
5x + 5x . 52 = 650
5x .( 1 + 25 ) = 650
5x . 26 = 650
5x = 650 : 26
5x = 25
5x = 52
=> x = 2
Vậy x = 2
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
a; - \(\dfrac{10}{13}\) + \(\dfrac{5}{17}\) - \(\dfrac{3}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{11}{20}\)
= - (\(\dfrac{10}{13}\) + \(\dfrac{3}{13}\)) + (\(\dfrac{5}{17}\) + \(\dfrac{12}{17}\)) - \(\dfrac{11}{20}\)
= - 1 + 1 - \(\dfrac{11}{20}\)
= 0 - \(\dfrac{11}{20}\)
= - \(\dfrac{11}{20}\)
b; \(\dfrac{3}{4}\) + \(\dfrac{-5}{6}\) - \(\dfrac{11}{-12}\)
= \(\dfrac{9}{12}\) - \(\dfrac{10}{12}\) + \(\dfrac{11}{12}\)
= \(\dfrac{10}{12}\)
= \(\dfrac{5}{6}\)
c; [13.\(\dfrac{4}{9}\) + 2.\(\dfrac{1}{9}\)] - 3.\(\dfrac{4}{9}\)
= [\(\dfrac{52}{9}\) + \(\dfrac{2}{9}\)] - \(\dfrac{4}{3}\)
= \(\dfrac{54}{9}\) - \(\dfrac{4}{3}\)
= \(\dfrac{14}{3}\)
1.
11/13.x=1
x=1:11/13
x=13/11
Vậy x=13/11
2.
-2/5x+4/3=7/3
-2,5x =7/3-4/3
-2,5x =3/3=1
x =1:(-2,5)
x =-0,4
Vậy x=-0,4
3.
x.6/25=15/-13
x =15/-13:6/25
x =-125/26
Vậy x=-125/26
4.
x:4/11=13/-45+8/15
x:4/11=11/45
x =11/45.4/11
x =4/45
Vậy x=4/45
5.
[(6/1/2):0,05/(7/1/20-5,65)+1/3/5]:2x=6